2015
DOI: 10.2174/1574884710666150609154741
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate Drug Use in People with Cognitive Impairment and Dementia: A Systematic Review

Abstract: The aim of this systematic review was to identify, assess and summarize studies about potentially inappropriate drug use (IDU) in cognitive impairment and dementia and to present findings about whether cognitive impairment and dementia are associated with IDU. The search was made in Medline/PubMed using free terms in the title or abstract. The inclusion criteria were: English language, published until 1 March 2014, original quantitative study and assessment of overall IDU with a consensus based summarized meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 45 publications
2
78
2
Order By: Relevance
“…The severity of cognitive impairment (measured by the MMSE score) was not associated with the risk of taking a Priscus PIM in our analysis. This result agrees with previous German and international studies that also failed to find associations between cognitive impairments or dementia and PIM use [49]. …”
Section: Discussionsupporting
confidence: 93%
“…The severity of cognitive impairment (measured by the MMSE score) was not associated with the risk of taking a Priscus PIM in our analysis. This result agrees with previous German and international studies that also failed to find associations between cognitive impairments or dementia and PIM use [49]. …”
Section: Discussionsupporting
confidence: 93%
“…In addition, STOPP-listed PIP involving nonsteroidal anti-inflammatory drugs (NSAIDs) were more frequent in people not dispensed medicines for dementia than people dispensed medicines for dementia, including long-term use of NSAIDs (11.3% vs 7.2%, P < .0001) ( green list) higher than that of participants without dementia. 26 In a study from the United States involving participants diagnosed with incident dementia and those without dementia, the prevalence of PIMs use in the 1-year period post diagnosis, as defined by the 2015 Beers criteria, was 69% in people with dementia versus 74% in those without dementia. 25 In contrast, a systematic review looking at PIP in people with dementia found that dementia was associated with a decrease in the likelihood of PIMs.…”
Section: Prevalence Of Individual Stopp Criteriamentioning
confidence: 99%
“…12 Previous studies have shown that frailty is associated with use of higher medication numbers and select drug classes, which may increase the risk of adverse drug events. 13,14 An extensive literature describes indicators of PIM use and prevalence in the nursing home, and characteristics associated with PIM prescribing, [15][16][17][18][19] but few studies have examined use of these medications during transition to nursing homes or in relation to frailty. Whether older adults enter nursing homes on these drugs (and whether any effort is made to discontinue PIMs following entry) or whether PIMs are introduced in nursing homes is of importance, particularly if patterns differ by frailty status.…”
mentioning
confidence: 99%